Agricultural innovation characteristics and their utilization: A case of National Agricultural Research Organization - Alex, Barekye (Kabale University, 2022)
A Dissertation Submitted to the Directorate of Postgraduate Training in Partial fulfilment of the Requirements for the Award of a Master of Business Administration of Kabale University